The ideal treatment timing for diabetic retinopathy: the molecular pathological mechanisms underlying early-stage diabetic retinopathy are a matter of concern - Sun, Wen-Jie; An, Xue-Dong; Zhang, Yue-Hong; Zhao, Xue-Fei; Sun, Yu-Ting; Yang, Cun-Qing; Kang, Xiao-Min; Jiang, Lin-Lin; Ji, Hang-Yu; Lian, Feng-Mei (Frontiers in Endocrinology, 2023)
Diabetic retinopathy (DR) is a prevalent complication of diabetes, significantly impacting patients' quality of life due to vision loss. No pharmacological therapies are currently approved for DR, excepted the drugs to treat diabetic macular edema such as the anti-VEGF agents or steroids administered by intraocular route. Advancements in research have highlighted the crucial role of early intervention in DR for halting or delaying disease progression. This holds immense significance in enhancing patients' quality of life and alleviating the societal burden associated with medical care costs. The non-proliferative stage represents the early phase of DR.In comparison to the proliferative stage, pathological changes primarily manifest as microangiomas and hemorrhages, while at the cellular level, there is a loss of pericytes, neuronal cell death, and disruption of components and functionality within the retinal neuronal vascular unit encompassing pericytes and neurons. Both neurodegenerative and microvascular abnormalities manifest in the early stages of DR. Therefore, our focus lies on the nonproliferative stage of DR and we have initially summarized the mechanisms involved in its development, including pathways such as polyols, that revolve around the pathological changes occurring during this early stage. We also integrate cutting-edge mechanisms, including leukocyte adhesion, neutrophil extracellular traps, multiple RNA regulation, microorganisms, cell death (ferroptosis and pyroptosis), and other related mechanisms. The current status of drug therapy for early-stage DR is also discussed to provide insights for the development of pharmaceutical interventions targeting the early treatment of DR.